2004
DOI: 10.1503/cmaj.1031205
|View full text |Cite
|
Sign up to set email alerts
|

Family caregiver burden: results of a longitudinal study of breast cancer patients and their principal caregivers

Abstract: Background: The vital role played by family caregivers in supporting dying cancer patients is well recognized, but the burden and economic impact on caregivers is poorly understood. We prospectively examined the psychosocial, occupational and economic impact of caring for a person with a terminal illness. Methods: We studied 89 caregivers of women with advanced breast cancer receiving care at either the Ottawa or Hamilton regional cancer centres in Ontario. Patients were followed until their death or study com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
681
10
53

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 796 publications
(784 citation statements)
references
References 37 publications
(35 reference statements)
40
681
10
53
Order By: Relevance
“…28 It has been very well established that family caregivers in general and those in oncology in particular have a high risk of depression because they experience chronic stress that affects their physical state. 29,30 In keeping with the results of the current study, 2 case-control studies of the risk for depression in the partners of cancer patients that had small samples but relevant comparison groups also found a significantly increased risk in the exposed group. 12,13 Although the outcomes of these 2 studies are less marked than in the current study, the results support the hypothesis that a partner's cancer diagnosis has an effect on the spouse's risk for depression.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…28 It has been very well established that family caregivers in general and those in oncology in particular have a high risk of depression because they experience chronic stress that affects their physical state. 29,30 In keeping with the results of the current study, 2 case-control studies of the risk for depression in the partners of cancer patients that had small samples but relevant comparison groups also found a significantly increased risk in the exposed group. 12,13 Although the outcomes of these 2 studies are less marked than in the current study, the results support the hypothesis that a partner's cancer diagnosis has an effect on the spouse's risk for depression.…”
Section: Discussionsupporting
confidence: 86%
“…34 Two follow-up studies also demonstrated a significantly increased risk of depression among individuals whose partner had cancer in the terminal stage. 10,15 Thus, the effect of breast cancer in a partner on the man's risk for hospitalization with depression might depend both on the burden of late effects of the breast cancer and treatment and the overall prognosis. 15 Previously, we conducted a nationwide, populationbased study to determine whether cancer is followed by an increased risk of divorce or separation in cohabiting partners, which might explain the increased risk of severe depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literatures showed risk for depression, anxiety, improper sleep and diminish QoL can increase in cancer caregivers (Awadalla et al, 2007;Chang et al, 2007;Northouse et al, 2005) and also they frequently report changes in their usual activities, including household and family activities, social and community activities, personal care, and occupational activities because of caregiving responsibilities (Coristine et al, 2003;Grunfeld et al, 2004).…”
Section: Introductionmentioning
confidence: 99%